Functional Capacity Evaluation for Work-Related Injuries to the Foot and Ankle is Associated with Low Return to Work Rate. Issue 4 (16th October 2019) - Idarraga, Alexander J.; Wright-Chisem, Adam; Bohl, Daniel D.; Lee, Simon; Lin, Johnny; Holmes, George B.; Hamid, Kamran S.
Category: Hindfoot, Ankle, Midfoot/Forefoot, Injury and Rehabilitation Introduction/Purpose: The functional capacity evaluation (FCE) is used to determine a worker's physical ability after treatment of a work-related injury. This evaluation is a critical determinant in the administration of benefits and the decision to return to work (RTW). The purpose of this study is to characterize FCE results and ability to RTW among patients treated for work- related orthopaedic injuries to the foot or ankle. Methods: A retrospective medical record review from the practices of four orthopaedic foot and ankle surgeons was conducted. Inclusion criteria were (1) treatment of a work-related injury to the foot or ankle, (2) at least 2 years of follow-up from the injury, and (3) documentation of an associated FCE. The FCE report and clinic notes were used to determine the patient's pre-injury job requirement (Department of Labor Office category: light, medium, or heavy), post-injury FCE-determined work ability (light, medium, or heavy), specific FCE- or physician-imposed work restrictions, and clearance for RTW. Patients were considered cleared to RTW if their FCE-determined work ability met or exceeded their pre-injury job requirement and if there were no additional restrictions imposed by the FCE or physician that would prevent them from functioning in their pre-injury role. Results: A total of 188 patients met inclusion criteria. Missteps/rotational injuries (44.1%), falls from height (22.3%), and crush injuries (20.7%) were the most common mechanisms. 74.4% of patients had FCE-determined work abilities at or above their pre- injury job requirements, and 63.3% of patients were eventually cleared for RTW. The median time from injury to clearance for RTW was 2.0 ± 1.3 years. Reasons for not being cleared to RTW included failure to meet the pre-injury job requirement (67.2%), specific FCE-imposed limitations (28.3%), or specific physician-imposed limitations (4.5%). Less strenuous pre-injury job requirement was positively associated with both FCE-determined work ability meeting pre-injury job requirement and clearance for RTW (p<0.001 and p=0.034, respectively; Table 1). Conclusion: Approximately two-thirds of patients undergoing FCE after a work-related foot or ankle injury are cleared to RTW. However, it takes a median of two years to achieve this clearance. Patients with jobs that are more physically strenuous are less likely to be able to return to those jobs after injury to the foot or ankle.